Completion time of CH4 hydrate formation in the presence of copper nanofluid - Nashed, O. (Alpha Publishers, 2020)
Research design on the toxicity of Sodium Dodecyl Urea (SDU) and Sodium Dodecyl Sulphides (SDS) copper nanofluid on kinetics of methane hydrate formation was studied. The experiments were done using stainless steel stirred reactor at 5.1 MPa pressure and 274.15 K temperature. Completion time was reported to describe overall formation kinetic. The consequences exposed that SDS and nanofluid reduced the completion time significantly. Among all samples 0.05wt copper nanoparticles suspended in The 0.03 weight percent SDS solution achieved the average formation of methane hydrate in shortest time. Nanofluid contains 0.01wt and 0.1wt copper nanoparticles do not enhance the hydrate formation in compare to 0.03 wt SDS solution. Â© 2020 Alpha Publishers.